Crematorium and Vertical Burial in Surabaya as Solution for Water Absorption in Urban Density Problem - Heristama A. Putra; Ima Defiana; Sri Nastiti N. Ekasiwi (Institut Teknologi Sepuluh Nopember, 2017)
Surabaya is the second largest city in Indonesia, which has many problems. Urban density is a major issue which has problems in it, starting from the population density up to the limitations of burial grounds that exist today. Design problem which arises is uniting the facility of funeral homes, crematoriums, and tombs in one area to reduce the mobilization on the road resulting in traffic density. Urban density has resulted in a couple of problems ranging from population density to scarcity of lands. Crematorium and vertical burial therefore become a crucial part of a city. While there has been less open green spaces, crematorium and vertical burial are expected not to reduce the open green spaces. Data scape as a design method is used to obtain design criteria for preliminary design. To obtain a form of structure, combination with the multiple addition geometry method is attempted. A design obtained by making vertical buriel footprint design that is able to provide sufficient absorption area by taking into account the percentage of urban open green space. To create a open green space and water absorption areas by lifting some mass of the building.